Answer: The required solution is x = 1 and y = -2.
Step-by-step explanation: We are given to solve the following system of equations using substitution, elimination by addition or augmented matrix methods :
![5x-3y=11~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\7x+4y=-1~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://img.qammunity.org/2020/formulas/mathematics/college/14pec85onaq57jnd53uur35pgvnjpx608d.png)
We will be using the method of SUBSTITUTION to solve the given system.
From equation (i), we have
![5x-3y=11\\\\\Rightarrow 5x=11+3y\\\\\Rightarrow x=(11+3y)/(5)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iii)](https://img.qammunity.org/2020/formulas/mathematics/college/b9h4l2yeqzkk7oov4ngdfz4nown1v8ho31.png)
Substituting the value of x from equation (iii) in equation (ii), we get
![7x+4y=-1\\\\\\\Rightarrow 7*(11+3y)/(5)+4y=-1\\\\\\\Rightarrow 77+21y+20y=-5\\\\\Rightarrow 41y=-5-77\\\\\Rightarrow 41y=-82\\\\\Rightarrow y=-(82)/(41)\\\\\Rightarrow y=-2.](https://img.qammunity.org/2020/formulas/mathematics/college/5olslzi72m5ndyrbqmn66f6j4fee62z7cf.png)
Putting the value of y in equation (iii), we get
![x=(11+3*(-2))/(5)=(11-6)/(5)=(5)/(5)=1.](https://img.qammunity.org/2020/formulas/mathematics/college/khfh05s6cvt5m8azdlj7soqzhzrh7i5nsv.png)
Thus, the required solution is x = 1 and y = -2.